An Archive of the Department of Educology - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 1999)
The publication contains archive material from the Department of Educology at Vilnius University which reveals the history of the department, most significant events in its life. This should serve as an incentive to publish the chronicles of departments of pedagogy from other universivities, their most important achievements and losses. People who served the improvement of Lithuanian education and pedagogical science should not be forgotten.